2011
DOI: 10.1186/2049-6958-6-3-155
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplant improves pulmonary hypertension in patients with end stage renal disease

Abstract: BackgroundPulmonary hypertension (PH) is present in a significant proportion of patients with end stage renal disease (ESRD) and is of prognostic importance. Data on the effect of renal transplant on PH is very limited. In this study, the aim was to examine the effect of renal transplant on systolic pulmonary artery pressure (SPAP) determined by Doppler echocardiography.MethodsAnalysis was performed on the records of 500 consecutive patients who underwent renal transplant at our center between the years 1999 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…The overall prevalence of elevated pulmonary pressure among patients undergoing renal transplantation in our analysis was 26.6%. This rate is similar to previous studies examining the prevalence of PH in end‐stage renal disease patients . Elevated pretransplant PASP did not increase 4‐year mortality or graft loss, but was associated with significantly decreased graft function manifesting with lower eGFR at 1 year and 2 years post‐transplantation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall prevalence of elevated pulmonary pressure among patients undergoing renal transplantation in our analysis was 26.6%. This rate is similar to previous studies examining the prevalence of PH in end‐stage renal disease patients . Elevated pretransplant PASP did not increase 4‐year mortality or graft loss, but was associated with significantly decreased graft function manifesting with lower eGFR at 1 year and 2 years post‐transplantation.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study reported that in patients undergoing pretransplant evaluation with transthoracic echocardiography (TTE), PH has been detected in 17% of patients with a mean pulmonary arterial systolic pressure (PASP) of 45.9 ± 8.8 mm Hg . Despite the high prevalence of PH in end‐stage renal disease patients considered for kidney transplantation, data on post‐transplant outcomes in patients with pretransplant mild‐to‐moderate PH are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time there are numerous observations of improvement in PHT along with other echocardiographic parameters after renal transplantation [1,12,25,26]. This has led many to propose that PHT can be used as an indication for expeditious renal transplantation [12,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A clear cutoff of severity of pulmonary artery pressures beyond which mortality risk increases is not well defined. It has been suggested that patients with mild to moderate PHT may be considered for expedited transplantation to prevent the PHT from worsening and potentially improve it [1,12,25,26] and severe PHT may be treated before transplantation to improve patient and graft outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Распро страненность ЛГ после успешной трансплантации почки (ТП) существенно ниже: порядка 5-14% [5]. Опубликованы результаты ряда исследований, сви детельствующие о значительном регрессе клинико инструментальных признаков ЛГ после ТП [6][7][8].…”
Section: Introductionunclassified